The Influence of Financial Literacy, Overconfidence, and Financial Behavior on Investment Decisions of Students of the Faculty of Economics and Business University of Pembangunan Nasional "Veteran" East Java - Priangga, Ilham Fajar; Purwanto, Eko (East Asian Journal of Multidisciplinary Research, 2024)
This study aims to determine the effect of financial literacy, overconfidence, and financial behavior on investment decisions of students of the Faculty of Economics and Business, University of Pembangunan Nasional East Java. The method applied in this study is a quantitative approach using stratified random sampling techniques. The sample of this study consisted of 98 respondents who had experience in making investment decisions. Data for this study was collected through filling out questionnaires distributed to students of the Faculty of Economics and Business University of Pembangunan Nasional "Veteran" East Java. Data analysis using Partial Least Square (PLS). The findings of this study show that financial literacy has no influence on investment decisions, overconfidence has a significant influence, and financial behavior has a significant influence on investment decisions.